DDRE-45. HIGH-THROUGHPUT SCREENING OF EPIGENETIC COMPOUNDS FOR THE TREATMENT OF CHORDOMA IDENTIFIES POTENTIAL NOVEL THERAPEUTICS. (12th November 2021) - Wroblewski, Tadeusz; Tatman, Philip; Fringuello, Anthony; Scherer, Sam; Foreman, William; Damek, Denise; Youssef, Samy; Lillehei, Kevin; Ormond, David; Graner, Michael
Abstract: BACKGROUND: Chordoma is a rare malignant tumor with few treatment options. While surgical resection is deemed the most effective treatment, the 5-year overall survival rate is 61% and 5-year recurrence free survival rate is approximately 50%. To date, no FDA approved pharmacotherapies exist for the treatment of chordoma, and adjuvant therapy remains highly debated. This necessitates the need for further research to provide clinicians with more options to treat this patient population. METHODS: In this study, we conducted a high-throughput 139-compound epigenetic inhibitor screen against 12 chordoma patient-derived cell lines; 4 were resected at our institution and 8 were graciously donated by the Chordoma Foundation. RESULTS: 8 tumors were located in the sacrum, 3 were located in the mobile spine, and 1 tumor was located in the clivus. 5 tumors were primary, 5 were recurrent, and 2 were metastatic. 6 tumors came from female patients and 6 tumors came from male patients. The top three most effect compounds across the cohort were the G9a inhibitor UNC0631 (cell viability = 64.5% +/-25.1SD; p=1.53x10 -9 ), the KDM inhibitor JIB-04 (cell viability = 68.4% +/-27.2SD; p=9.81x10 -8 ), and the G9a inhibitor BIX01294 (cell viability = 68.6% +/-27.9SD; p=1.27x10 -7 ). No single compound significantly reduced viability in every tumor in the cohort, although the HDAC inhibitor HC Toxin significantly reduced viability in 9 tumors (cell viability = 69.7% +/-16.6SD; p=2.6x10 -12 ). The most effective compound for sacral tumors was UNC0631 (viability = 68.6% +/-22.1SD; p=4x10 -7 ), UNC0631 was also the most effective for spinal tumors (viability = 54.4% +/-32.1SD; p=2.72x10 -3 ), and notably, no significant compounds were identified for the single clival tumor. CONCLUSIONS: Based on our drug screen results, epigenetic inhibition, particularly methyltransferase inhibition, may be a promising therapeutic avenue for the treatment of chordomas.